DISPARITAS PENETAPAN PENGADILAN TERHADAP PERMOHONAN PERKAWINAN PASANGAN BERBEDA AGAMA - Tunggu, Rafael (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The title of the research is Disparity in Court Determinations Regarding Marriage Applications for Couples of Different Religions. The problem to be answered is how the District Court responds to marriage requests from couples of different religions in Indonesia, whether all requests are rejected or whether there is a disparity, namely some are rejected and some are granted. Apart from that, we also want to know the judge's considerations in both rejecting and granting marriage requests for couples of different religions. The method used in this research is a normative legal research method, namely legal research on principles, doctrines (teachings), norms, rules of statutory regulations, and court decisions. The analysis was carried out descriptively-qualitatively by criticizing the judge's considerations using several approaches, namely conceptual, statutory and comparative. The results of the research show that there is disparity in court decisions regarding marriage applications between couples of different religions. In the Surakarta District Court's decision Number 403/Pdt.P/2019/PN Skt, the judge rejected the application of a couple of different religions on the grounds that the parties did not enter into a marriage based on religion in accordance with the orders of Article 2 paragraph (1) of Law Number 1 of 1974 in conjunction with Number 16 of 2019 concerning Marriage. In the Determination of the Surakarta District Court Number: 278/Pdt.P/2019/PN.Skt, the judge granted the marriage request of a couple of different religions on the basis that the parties had entered into a marriage according to the procedures of the Catholic Church, which shows that the Muslim parties had submitted to voluntarily comply with Catholic marriage procedures, which thus fulfills the demands of Article 2 paragraph (1) of Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 concerning Marriage. These two court decisions are guided by the Letter of the Registrar of the Supreme Court of the Republic of Indonesia Number 231/PAN/HK.05/1/2019 dated 30 January 2019 in response to the letter of the Director General of Population and Civil Registration of the Ministry of Home Affairs Number 472.2/18752/DUKCAPIL dated 10 October 2018 concerning Marriage Registration different religions, which in essence allows registration if a marriage has taken place according to one of the religions adhered to by the parties. With the issuance of SEMA Number 2 of 2023 concerning Instructions for Judges in Adjudicating Cases on Applications for Registration of Marriages Between People of Different Religions and Beliefs, judges are not permitted to grant applications for registration of marriages between people of different religions.